What do the consequences of environmental, social and governance failures tell us about the motivations for corporate social responsibility? - Richard Walton (International Journal of Financial Studies, 2022)
This paper investigates the motivations behind corporate social responsibility (CSR) by considering the consequences of environmental, social and governance (ESG) failures that CSR is intended to avoid. Using data from 2581 public U.S. firms over 2007-2018, this paper finds that such failures are associated with increased CEO turnover. This relationship is driven primarily by CEOs with longer tenures and by environmental issues. These negative events are also found to be associated with declines in the firm's sales growth, employment growth and equity returns. CSR activities that reduce the incidence of such events therefore benefit both the CEO and the shareholder. Interestingly, replacing the CEO does not mitigate the negative impacts of such events on the firm, nor does it reduce the incidence of such events in subsequent years. The decision to remove the CEO following such failures appears costly to both the CEO and the firm's shareholders.
Keywords: 330; CEO turnover; corporate governance; corporate social responsibility (CSR); firm performance